Investigation on the performance of macro electrochemical machining of the end face of cylindrical parts. (1st March 2020) - Liu, Yang; Qu, Ningsong
Abstract: At present, the cylindrical parts have been widely used in aerospace and other industrial fields. But it is difficult to machine the surface of cylindrical parts by traditional machining methods, because most of these parts are made from the difficult-to-cut materials. Electrochemical machining (ECM) has the characteristic of no tool wear and no residual stress, which has been widely used in the machining of difficult-to-cut material. But, little research related to the electrochemical machining of the end face of cylindrical parts has been reported, although this research is of great significance to the machining of cylindrical parts. Therefore, an electrochemical machining method for machining the end face of the cylindrical parts was proposed in this paper. Based on the distribution of the electric field, the end face of the tool electrode was designed as a fan-shape. Through the numerical simulation and theoretical analysis of the flow field, the gradually varied narrow slit outlet was designed to obtain a uniform machining flow field. Moreover, the side of the cathode tool was designed as contractive inward to reduce the flow resistance of electrolyte, promote the removal of electrolytic products and reduce the pitting corrosion. Experiments were conducted to verify the proposed method and improved tool, the results showed that the pitting corrosion near the edge of the machined areas significantly reduced and the machining surface smoothness improved when the cutting depth reached 0.3 mm. A flat machined surface could be obtained on the end face of the cylindrical part. Besides, the machining repeatability and surface smoothness were both high enough to make this method be applied in industrial production in the future. Highlights: A vertical electrochemical turning process method for machining the end face of the revolving parts, whose machining repeatability and machining surface smoothness are both good. The tool with fan-shaped end face and gradient outlet could improve the processing uniformity. The tool with the side contractive inward can reduce the flow resistance of electrolyte, promote the removal of electrolytic products and reduce the pitting corrosion when the cutting depth reached a certain value.